Photovoltaic cells based on sequentially adsorbed multilayers of conjugated poly(p-phenylene ethynylene)s and a water-soluble fullerene derivative - Mwaura, Jeremiah K (Langmuir : the ACS journal of surfaces and colloids, 2005)
We describe the layer-by-layer (LBL) fabrication of multilayer films and photovoltaic cells using poly(phenylene ethynylene)-based anionic conjugated polyelectrolytes as electron donors and water-soluble cationic fullerene C60 derivatives as acceptors. LBL film deposition was found to be linearly related to the number of bilayers as monitored by UV-vis absorption. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) of the multilayer films revealed an aggregated but relatively uniform morphology devoid of any long-range phase separation. The maximum incident monochromatic photon to current conversion efficiency (IPCE) of the photovoltaic cells was 5.5%, the highest efficiency reported to date for cells fabricated by using the LBL fabrication technique, and since the thin film cells do not provide complete absorption of the incident light, the current generation per photon absorbed may be as much as 10%. The cells exhibited open circuit voltages of 200-250 mV with highest measured short circuit currents up to 0.5 mA/cm2 and fill factors around 30%. The power conversion efficiencies measured at AM 1.5 solar conditions (100 mW/cm2) varied between 0.01 and 0.04%, and similar to the IPCE results, the efficiency is a function of the thickness of the PV active layer